Facies and sequence architecture of a tropical foramol-rhodalgal carbonate ramp: Miocene of the central Apennines (Italy) - BRANDANO, Marco; CORDA, Laura; CASTORINA, Francesca (WILEY-BLACKWELL, 2010)
Integrated data from sedimentological and microfacies analyses have been used to reconstruct the stratigraphic and architectural evolution of a carbonate ramp exposed in the central Apennines. The platform was a wide homoclinal ramp characterized by rhodalgal, bryomol and foramol skeletal-grain associations that developed under tropical-subtropical conditions. Based on facies distribution and palaeoecology, the ramp can be subdivided into: (1) an inner zone whose main components include balanids, molluscs and branching red algae; (2) a middle zone characterized by rhodolitlis and larger foraminifera; and (3) an outer ramp consisting of: (a) a proximal zone dominated by bryozoan colonies, bivalves and echinoids: (b) an intermediate zone where the main components are benthic and planktonic foraminifera, worm tubes, fragmented echinoids and bivalves; and (c) a distal zone where marls and calcarenites contain silica-sponge spicules, planktonic foraminifera and mollusc-bryozoan-echinoid debris.